Co-transplantation of Human Fetal Mesenchymal and Hematopoietic Stem Cells in Type 1 Diabetic Mice Model - Arjmand, Babak; Goodarzi, Parisa; Aghayan, Hamid Reza; Payab, Moloud; Rahim, Fakher; Alavi-Moghadam, Sepideh; Mohamadi-jahani, Fereshteh; Larijani, Bagher (Frontiers in Endocrinology, 2019)
Introduction Cell therapy can overcome the limitation of conventional treatments (including different medications and β cell replacement) for type 1 diabetes. Based- on several studies human fetal mesenchymal and hematopoietic stem cells are ideal candidates for stem cell therapy. On the other hand, co-transplantation of them can improve their effects. Accordingly, the aim of this research is co-transplantation of human fetal mesenchymal and hematopoietic stem cells in type 1 diabetes. Materials and Methods The liver of legally aborted fetus was harvested. Then, mononuclear cells were isolated and extracted mesenchymal stromal cells and CD34+ hematopoietic stem cells were cultured. Expression of pluripotency markers were evaluated. For molecular imaging, mesenchymal stromal cells were labeled using GFP- vector. BALB/c inbred male mice were modeled by injection a single dose of Streptozotocin. Diabetic animals were received stem cells. After stem cell transplantation, in vivo imaging was performed and blood glucose levels were measured weekly. Results Fetal mesenchymal stromal cells were demonstrated differentiation potential. Expression of pluripotency markers were positive. The mean of blood glucose levels were reduced in mixed mesenchymal and hematopoietic stem cells transplantation. A lot of GFP-labeled mesenchymal stem cells were engrafted in the pancreas of animal models that received a mixed suspension of hematopoietic and mesenchymal stromal cells. Conclusions Human fetal stem cells are valuable source for cell therapy and co-transplantation of mesenchymal stromal cells can improve therapeutic effects of hematopoietic stem cells.